Avaliação dos dados epidemiológicos, fatores de risco e alterações em mamografia e/ou ultrassonografia para câncer de mama em portadoras Neoplasia Endócrina Múltipla Tipo 1 - Ramírez, Eleicy Margarita Hernández (2022)
Breast cancer represents the leading cause of cancer death in the Brazilian female population. Studies have shown that MEN-1 patients have an increased risk of developing breast cancer earlier. MEN-1 is considered a complex and multisystemic disease, characterized by the loss of the MEN1 tumor suppressor gene. New screening protocols are needed to assess possible breast cancer risks in this population. Objective: To evaluate epidemiological data, risk factors for breast cancer and changes in mammograms and/or ultrasound in MEN-1 carriers. Methodology: Cross-sectional, observational study, with interviews being carried out with 56 patients (p), all female, with a clinical and/or molecular diagnosis of MEN-1, being evaluated the epidemiological characteristics, obstetrical and occupational history and risk factors for cancer breast and MEN-1. To assess the presence of breast alterations, mammography and/or USG findings were analyzed and classified by the BI-RADS system as low risk (1-3), high risk (4-6) or diagnosis of breast cancer, being compared by the Fisher's exact test, with significance of p < 0.05. Results: Of the total of 56p, 33 completed the entire study protocol. The mean age was 48.7±1.8 years and the BMI was 27.56±0.73 kg/m2, 18% of whom were obese. The report of dyslipidemia was observed in 39% and diabetes mellitus 2 in 36%. Menopause occurred on average at 47.7±1.4 years and 45% had a family member with breast cancer. 28 (85%) patients were considered at low risk for breast cancer and 5 (15%) as high risk. Three patients (9%) were diagnosed with Luminal B type breast cancer. There was a higher frequency of exposure to toxic agents (p=0.01), low education (p=0.04) and absence of breastfeeding (p= 0.02) in the group with high-risk findings for breast cancer. Conclusion: We observed the presence of risk factors related to breast cancer among women with MEN-1 and changes in screening tests classified as high risk or diagnosed in 15%, with factors such as exposure to toxic agents, low level of education and lack of breastfeeding were the most frequent findings. The factors described in the research may also bring additional risks to MEN-1 carriers. Thus, the development of an earlier systematic screening program is necessary in this population.